The long-term effects of alcohol availability on mortality: Evidence from an alcohol reform - Henri Salokangas (Aboa Centre for Economics (ACE), 2016)
I examine the long-term mortality effects of an exogenous shock in alcohol availability using Census data, mortality data and data on distance to alcohol outlets. In 1969, Finland underwent significant changes in alcohol availability both via Minimum Legal Drinking Age (MLDA) and distribution channels. The geographical alcohol availability increased especially for the previously "dry" rural Finland. The main results suggest that reducing MLDA from 21 to 18 had a positive effect on alcohol-related deaths in the long term for the 18-19 year-olds that were immediately affected by MLDA. I do not find evidence that the reduction of physical alcohol availability in rural areas resulted into diminishing difference of alcohol-related death rates between urban and rural areas.
Keywords: I12; L43; R11; 330; Health Behavior; Deregulation; Regional Economic Activity